2016
DOI: 10.1159/000443527
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Obstructive Sleep Apnea and Tobacco Smoking on Endothelial Function

Abstract: Background: Endothelial dysfunction has been recognized to occur in the context of obstructive sleep apnea (OSA) or tobacco smoking. However, the deleterious effect on vascular function with concurrence of both conditions is largely unknown. Objective: To investigate whether the concurrence of OSA and smoking poses an additive detriment to endothelial dysfunction. Methods: Chinese men without a history of chronic medical illness were invited to complete a questionnaire including smoking pack-year exposure, pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
(59 reference statements)
0
12
0
1
Order By: Relevance
“…This meta‐analysis investigated the available evidence on the association between OSA and alcohol, caffeine and tobacco. Studies indicate associations between tobacco and OSA, and alcohol and OSA, however, conclusive evidence was not found until now. Based on the current available literature and on the eligibility criteria established for this systematic review, results indicate OSA is to be associated with the use of alcohol, but there is not enough scientific evidence to confirm the association between OSA and tobacco.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This meta‐analysis investigated the available evidence on the association between OSA and alcohol, caffeine and tobacco. Studies indicate associations between tobacco and OSA, and alcohol and OSA, however, conclusive evidence was not found until now. Based on the current available literature and on the eligibility criteria established for this systematic review, results indicate OSA is to be associated with the use of alcohol, but there is not enough scientific evidence to confirm the association between OSA and tobacco.…”
Section: Discussionmentioning
confidence: 92%
“…It is worth noting that the question “was the follow‐up carried out over a sufficient time period?” was considered not applicable for the included studies, since none of them proposed longitudinal results. Of the 11 studies included had moderate risk of bias, and 2 as low risk of bias . Decisions regarding individual domains within the ‘Risk of bias’ tool were observed in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…As OSAS and smoking often co-occur, they may share common oxidative and inflammatory pathways that contribute to lipid and glucose metabolic dysfunction 4 . Several previous cross-sectional studies have shown that the interaction between smoking and OSAS leads to increased endothelial dysfunction 17 , cognitive impairment 18 , and cardiovascular risk 19 . However, no study has explored the interaction between OSAS and smoking on glucose and lipid abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Zhu et al 13 have shown that smoking and OSA jointly cause insulin resistance and have synergistic effects on metabolic disorders. Lui et al 14 have also suggested that the coexistence of CIH and smoking causes severe endothelial dysfunction. Studies have also suggested that coexistence of both OSA and smoking leads to more severe cognitive dysfunction than any single factor 15 .…”
Section: Introductionmentioning
confidence: 99%